Growth of β-glycine crystals promoted by standing surface acoustic waves (SSAWs). Issue 9 (8th February 2018) - Bai, Cheng; Wang, Chaohui; Zheng, Tengfei; Hu, Qiao
Abstract : Glycine has three polymorphic forms, the α-, β- and γ-phase, where the β-phase is less stable than the other two, but it is the most useful one. Abstract : Glycine has three polymorphic forms, the α-, β- and γ-phase, where the β-phase is less stable than the other two, but it is the most useful one. In this work, the acoustic streaming induced by standing surface acoustic waves (SSAWs) has a significant influence on the crystallization of glycine. On the one hand, with the increase in the frequency of SSAWs, the kinetic effect of the SSAWs will improve the rate of supersaturation generation during the nucleation stage then the growth of the less stable form β-glycine will be promoted. On the other hand, with the increase of the input power, the thermal effect of the SSAWs will raise the temperature of the solution droplet then accelerate the solvent evaporation, thus shortening the crystallization period. Besides, under an extremely acidic condition, SSAWs can also promote the growth of the less stable phase α-glycine.